2000
DOI: 10.1177/0165551004233014
|View full text |Cite
|
Sign up to set email alerts
|

Information communication networking in rural communities: the case of women in Imo State, Nigeria

Abstract: This research focuses on exploring the existence or otherwise of any interactive information communication networks among women in Imo State. Using questionnaire and oral interview techniques, data were collected from 600 women, purposively chosen, covering the three senatorial zones of the State. Results show the existence of vibrant interactive networks among women, carried out on two levels: (i) diffused or non-restrictive patterns and (ii) restrictive or discriminatory patterns. Social, economic, political… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…There have been some studies on women's access to information in rural Africa (Nginwa et al, 1997;Uhegbu, 2000), but these studies confirmed the need for conceptual and/or methodological improvements in research. Mutua (1997, p. 74) for example, recommended that: Further investigation is required as to how women's groups might provide the information structure for the community as a whole .…”
Section: Research Contextmentioning
confidence: 99%
“…There have been some studies on women's access to information in rural Africa (Nginwa et al, 1997;Uhegbu, 2000), but these studies confirmed the need for conceptual and/or methodological improvements in research. Mutua (1997, p. 74) for example, recommended that: Further investigation is required as to how women's groups might provide the information structure for the community as a whole .…”
Section: Research Contextmentioning
confidence: 99%
“…Another part of the status problem is women's secretiveness, being too often unwilling to interact with one another and share information. This more often than not fuels ignorance, misunderstanding, fear, rumour and gossip (Uhegbu, 2000).…”
Section: Status Of Rural Women In Nigeriamentioning
confidence: 99%
“…This situation could be a result of what Nwokocha and Uhegbu (2000) deem to be the use of inappropriate channels of information dissemination which do not ensure accessibility to HIV/AIDS information. Research by Uhegbu (2000) has shown that the mass media are not easily accessible to many rural Nigerians due to factors such as poverty and illiteracy. The solution to combating the continued HIV/AIDS ignorance of the rural women therefore lies in adopting more accessible, convenient, familiar and cost-effective dissemination methods which could usher in a new understanding and appreciation of the reality of HIV/AIDS in Nigeria.…”
Section: Dissemination Of Hiv/aids Informationmentioning
confidence: 99%
“…These are the contending forces this writer saw, and was moved to carry out this investigation because there is an urgent need to unravel these forces that impede interactive interpersonal information networking among rural women in Imo State. (1) To determine the social, economic, political and other factors that constrain effective interactive interpersonal information networking among rural women; (2) To establish the effect of the factors on the mode of interaction among them; (3) To find out whether biology (nature) or some other factors negatively affect interaction among women; (4) To highlight the nature of the information they disseminate and the mode of dissemination; and (5) To find solutions to the problems identified.…”
Section: The Problemmentioning
confidence: 99%